In vivo measurements of blood viscosity and wall stiffness in the carotid using PC-MRI - Avril, Stephane; Huntley, Jonathan M.; Cusack, Rhodri (European Journal of Computational Mechanics, 2009)
A method is proposed for deducing blood viscosity and wall stiffness in the carotid from Phase-Contrast MRI data. The approach is based on Womersley’s model of blood flow derived from the resolution of the Navier-Stokes equations, assuming blood as a Newtonian fluid and the artery as a linear elastic cylindrical pipe. After presenting its principle, the approach is applied to the experimental data obtained on a single volunteer. Promising results are obtained.